Formulation and optimization of avocado (Persea americana) seed oil and extract in sunscreen lotion: physicochemical and in vitro photoprotective evaluation - Fasya Nadhira Sariful; Lina Winarti (Pharmaciana, 2026)
Ultraviolet (UV) radiation exerts detrimental effects on the skin, including erythema, premature aging, enhanced melanogenesis, and an increased risk of skin malignancies; therefore, sunscreen application is essential for effective photoprotection. Avocado seed oil and its extract demonstrate considerable promise as natural photoprotective agents due to their antioxidant capacity to scavenge free radicals and their UV-absorbing constituents. This study was designed to investigate the influence of different concentrations of avocado seed oil and its extract on the physicochemical characteristics of lotion formulations and their in-vitro sunscreen performance. The evaluated physicochemical parameters comprised organoleptic properties, pH, viscosity, spreadability, adhesion, and homogeneity. Sunscreen efficacy was determined by measuring the sun protection factor (SPF), percentage of transmission pigmentation (%Tp), and percentage of transmission erythema (%Te). Five formulations were optimized using a simplex lattice design implemented in Design-Expert® version 13, with response variables including SPF, %Te, %Tp, spreadability, adhesion, and viscosity. All formulations complied with established quality requirements, exhibiting pH values within the range of 4.5–8 according to SNI 16-4399-1996, viscosities between 2,000 and 50,000 cP, spreadability of 5–7 cm, and adhesion times greater than 4 seconds. Avocado seed oil significantly influenced viscosity and photoprotective parameters (SPF, %Te, and %Tp), whereas the extract predominantly affected spreadability and adhesion; both components contributed to pH variation. The optimal formulation consisted of 4.58% avocado seed oil and 10.41% extract, yielding predicted values of SPF 14.38, %Te 1.014, %Tp 1.009, spreadability 5.31 cm, adhesion time 5.60 seconds, and viscosity 2432.49 cPa·s, with an overall desirability value of 0.628. Collectively, these findings indicate that avocado seed oil and its extract significantly modulate both the physicochemical attributes of the lotion and its photoprotective efficacy, supporting their potential application as natural sunscreen agents.